Study of Mechanical Behavior in Epiphyseal Fracture Treated by Reduction and Cement Injection: No Immediate Post-Operative Weight-Bearing but Only Passive and Active Mobilization Should be Advised - Moufid, A.; Bokam, P.; Harika-Germaneau, G.; Severyns, M.; Caillé, L.; Valle, V.; Vendeuvre, T.; Germaneau, A. (Frontiers in Bioengineering and Biotechnology, 2022)
The development of new per-cutaneous techniques using a balloon for the reduction and cement for the stabilisation for the treatment of tibial plateau fractures (TPF) are promising. The biomechanical changes brought by the cement in the periarticular fracture is unknown. The objective of this study was to provide elements of understanding of the bone behaviour on an epiphyseal fracture treated with cementoplasty and to define the modifications brought about by the presence of this cement in the bone from both an architectural and biomechanical point of view. In vitro animal experimentation was conducted. Bones samples were prepared with a cavity created with or without cancellous compaction thanks to balloon expansion with the same protocol as in the treatment of TPF. A uniaxial compression test was performed with various speeds and by using Heaviside Digital Image Correlation to measure mechanical fields. Preliminary finite element models were constructed with various boundary conditions to be compared to our experimental results. The analysis of the images permits us to obtain a representative load vs time response, the displacement fields and the strain distribution for crack initiation for each sample. Microcracks and discontinuity began very early at the interface bone/cement. Even when the global behaviour was linear, microcracks already happened. There was no strain inside the cement. The finite element model that matched our experiments had no link between the two materials. In this work, the use of a novel correlation process highlighted the biomechanical role of the cement inside the bone. This demonstrated that there is no load transfer between bone and cement. After the surgery, the cement behaves like a rigid body inside the cancellous bone (same as a screw or plate). The cement provides a good reduction and primary stabilization (mini-invasive approach and good stress distribution) permitting the patient to undergo rehabilitation with active and passive mobilization, but no weight-bearing should be authorized while the cortical bone is not consolidated or stabilized.